2022
DOI: 10.3390/ani12162049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sources and Methods for the Isolation of Equine Adipose Tissue-Derived Stromal/Stem Cells and Preliminary Results on Their Reaction to Incubation with 5-Azacytidine

Abstract: Physiological particularities of the equine heart justify the development of an in vitro model suitable for investigations of the species-specific equine cardiac electrophysiology. Adipose tissue-derived stromal/stem cells (ASCs) could be a promising starting point from which to develop such a cardiomyocyte (CM)-like cell model. Therefore, we compared abdominal, retrobulbar, and subcutaneous adipose tissue as sources for the isolation of ASCs applying two isolation methods: the collagenase digestion and direct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…In the present study, however, not only induced cells were affected by this downregulation, but also NC, so that cardiomyogenic differentiation activity was excluded. That this downregulation can be associated with the occurrence of senescence in cells has already been discussed in detail in Trachsel et al [59]. While some studies demonstrated that BMPs possess a cardiomyogenesis-promoting effect [106,111,112], other research groups showed that transient inhibition of BMPs is necessary for in vitro cardiomyogenesis [25,113].…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…In the present study, however, not only induced cells were affected by this downregulation, but also NC, so that cardiomyogenic differentiation activity was excluded. That this downregulation can be associated with the occurrence of senescence in cells has already been discussed in detail in Trachsel et al [59]. While some studies demonstrated that BMPs possess a cardiomyogenesis-promoting effect [106,111,112], other research groups showed that transient inhibition of BMPs is necessary for in vitro cardiomyogenesis [25,113].…”
Section: Discussionmentioning
confidence: 83%
“…Sample collection and isolation of equine ASCs have already been published in our previous study [ 59 ]. In brief, equine abd, rb and sc adipose tissue from n = 16 horses (mares, geldings, stallions; median age [interquartile range]: 13.5 [18.0] years) was harvested after euthanasia at the Equine Clinic: Surgery and Radiology, Department of Veterinary Medicine, Freie Universität (FU) Berlin or slaughter in commercial slaughterhouses up to a maximum of 8 h post mortem.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations